2020
DOI: 10.3390/neurolint12030012
|View full text |Cite
|
Sign up to set email alerts
|

M Mode Ultrasound and Tissue Doppler Imaging to Assess Diaphragm Feature in Late Onset Pompe Disease

Abstract: Late-onset Pompe disease (LOPD) is an autosomal recessive lysosomal storage disease. Clinical features include skeletal muscle deficiency and diaphragm weakness. Clinical management relies on supportive treatment and mechanical ventilation in patients with chronic respiratory failure. M mode ultrasound and sniff tissue Doppler imaging can be used to assess and follow diaphragm function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Prior ultrasonographic assessments of tongue musculature indicated worsening fibrofatty replacement of muscles and increased EI of tongue musculature with LOPD when compared to healthy controls [ 20 ]. Multiple studies have identified ultrasonographic evidence of diaphragm involvement in LOPD, assessing diaphragm excursion, thickness at functional residual capacity, and thickness at total lung capacity but EI was not assessed in these studies [ [21] , [22] , [23] , [24] ]. Future studies may include ultrasonographic measurement of EI in the diaphragm, but technical difficulties of imaging such a thin muscle may complicate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Prior ultrasonographic assessments of tongue musculature indicated worsening fibrofatty replacement of muscles and increased EI of tongue musculature with LOPD when compared to healthy controls [ 20 ]. Multiple studies have identified ultrasonographic evidence of diaphragm involvement in LOPD, assessing diaphragm excursion, thickness at functional residual capacity, and thickness at total lung capacity but EI was not assessed in these studies [ [21] , [22] , [23] , [24] ]. Future studies may include ultrasonographic measurement of EI in the diaphragm, but technical difficulties of imaging such a thin muscle may complicate assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive simple and reproducible ultrasound and tissue Doppler imaging of the diaphragm also provide an ability to monitor and assess vital diaphragm function in PD patients. 11,[57][58][59] Classically, the drop of VC from upright to supine position is an indirect measure of diaphragm weakness, however, diaphragm weakness characterized by a paradoxical motion during a sniff test, has been observed utilizing M-mode ultrasound and tissue Doppler imaging techniques in a patient diagnosed with LOPD. 57 Furthermore, 17 LOPD patients were included in a study to evaluate the correlation between diaphragm thickness and mobility using ultrasonography and respiratory function using spirometry.…”
Section: Imagingmentioning
confidence: 99%
“…11,[57][58][59] Classically, the drop of VC from upright to supine position is an indirect measure of diaphragm weakness, however, diaphragm weakness characterized by a paradoxical motion during a sniff test, has been observed utilizing M-mode ultrasound and tissue Doppler imaging techniques in a patient diagnosed with LOPD. 57 Furthermore, 17 LOPD patients were included in a study to evaluate the correlation between diaphragm thickness and mobility using ultrasonography and respiratory function using spirometry. 58 Diaphragm excursion, thickness at functional residual capacity and total lung capacity, and thickness fraction were decreased and significantly correlated with the routine PFTs and other respiratory tests.…”
Section: Imagingmentioning
confidence: 99%